Filosofis Kehidupan Marga Silalahi dalam Suku Batak Terhadap Pancasila Sila Pertama Ketuhanan Yang Maha Esa - Marly Meani Silalahi; Yakobus Ndona (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
This study aims to analyze the life philosophy of the Silalahi clan within the Batak ethnic group and its relation to the First Principle of Pancasila, namely, Belief in One Supreme God. The research utilizes a qualitative descriptive method. This study explores the religious and cultural values upheld by the Silalahi clan and how these values align with the principle of Belief in One Supreme God. The findings reveal that the Silalahi clan holds a life worldview deeply grounded in strong religious and spiritual faith. These values are reflected through various traditional ceremonies, religious rituals, and life principles that emphasize harmony and piety towards God. Therefore, there is a substantial correlation between the life philosophy of the Silalahi clan and the First Principle of Pancasila, demonstrating how traditional values can reinforce national identity.